2009
DOI: 10.1007/dcr.0b013e31819a3ec0
|View full text |Cite
|
Sign up to set email alerts
|

Unroofing and Marsupialization vs. Rhomboid Excision and Limberg Flap in Pilonidal Disease

Abstract: The unroofing and marsupialization procedure provides more clinical benefits in the treatment of pilonidal disease than rhomboid excision and Limberg flap and should be considered the procedure of choice. However, it may be associated with more inconvenience in wound care and longer healing time than rhomboid excision and Lindberg flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 26 publications
4
66
1
10
Order By: Relevance
“…Treatment of pilonidal sinus disease contains many different techniques from simple drainage to complicated flaps (8)(9)(10)13). The treatment may vary with the disease condition and the surgeon's experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of pilonidal sinus disease contains many different techniques from simple drainage to complicated flaps (8)(9)(10)13). The treatment may vary with the disease condition and the surgeon's experience.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many different opinions regarding the surgical treatment of pilonidal sinus disease in the literature, the common issues are that surgery should be simple and easily applicable, that the hospital length of stay should be short, with less postoperative wound care and pain, low recurrence rates and short period to return to daily activities (4)(5)(6). That is why various surgical techniques like sinotomy, marsupialization, Karydakis, oblique primary repair and flap techniques have been applied and compared for many years (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of cosmetic outcome was evaluated only a few studies. Karakayal› et al 19 reported a small but statistically significant preference for off-midline closure than for midline closure, where satisfaction was measured by using a 0-10 visual analogue scale. Interestingly, Holmebakk et al 20 reported postoperative cosmetic result was satisfactory only in 42% of patients; the result was poor in 30% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…La técnica ideal para resolver esta patología debiera ser simple, tener una rápida recuperación y baja recidiva 1 . La técnica abierta más utilizada es la marsupialización con recidivas cercanas al 3%, sin embargo, esta téc-nica requiere de curaciones de hasta 40 días hasta su cicatrización completa [3][4][5]7 . Con la técnica de Karydakis el retiro de los puntos se realiza a los 15 días en forma rutinaria, sin requerir más cuidados de la cicatriz en el 94% de los casos luego de este plazo.…”
Section: Discussionunclassified
“…Estos hechos han motivado la descripción de múltiples técnicas, algunas más conservadoras desde cuidados de la zona sacrocoxígea hasta otras más definitivas, consistiendo en cirugías que ya sea dejan la herida abierta o practican cierre primario de ésta, siendo aún discutido cual es la mejor técnica 1,2 . Aunque las técnicas abiertas describen baja recidiva, requieren de tiempo prolongado de cicatrización y curaciones [3][4][5] . Respecto a las técnicas cerradas, en la última década se ha demostrado que los procedimientos con cierre asimétrico presentan menor recidiva que las de simple cierre primario en la línea media pudiendo estas últimas presentar recidivas de hasta 20% 6,7 .…”
Section: Introductionunclassified